2019
DOI: 10.1038/s41598-019-48885-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of methylcitrate and methylcitrate to citrate ratio in dried blood spots as biomarkers for inborn errors of propionate metabolism

Abstract: Deficiency of propionyl-CoA carboxylase causes propionic acidemia and deficiencies of methylmalonyl-CoA mutase or its cofactor adenosylcobalamin cause methylmalonic acidemia. These inherited disorders lead to pathological accumulation of propionyl-CoA which is converted in Krebs cycle to methylcitrate (MCA) in a reaction catalyzed by citrate synthase. In healthy individuals where no propionyl-CoA accumulation occurs, this enzyme drives the condensation of acetyl-CoA with oxaloacetate to produce citric acid (CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 22 publications
(40 reference statements)
1
20
0
Order By: Relevance
“…10 Another study analyzed the DBS concentration of MCA (and the MCA/citric acid ratio) and of methylmalonic acid in two MMA patients, one B12 responsive and the other B12 unresponsive, in relation to treatment initiation. 13 In the B12 responsive patient, MCA (and the MCA/citric acid ratio), adequately predicted the response to treatment in a similar manner as methylmalonic acid. A very recent study, analyzing in detail longitudinal data from clinical chemistry analysis and metabolic assays over the life course in 11 PA and 13 MMA patients, confirmed the direct link between ammonia and MCA and found that plasma and urine MCA levels were not significantly altered when samples were collected during episodes of metabolic decompensation.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…10 Another study analyzed the DBS concentration of MCA (and the MCA/citric acid ratio) and of methylmalonic acid in two MMA patients, one B12 responsive and the other B12 unresponsive, in relation to treatment initiation. 13 In the B12 responsive patient, MCA (and the MCA/citric acid ratio), adequately predicted the response to treatment in a similar manner as methylmalonic acid. A very recent study, analyzing in detail longitudinal data from clinical chemistry analysis and metabolic assays over the life course in 11 PA and 13 MMA patients, confirmed the direct link between ammonia and MCA and found that plasma and urine MCA levels were not significantly altered when samples were collected during episodes of metabolic decompensation.…”
Section: Discussionmentioning
confidence: 83%
“…8,9 Thus far, MCA has been mainly considered a helpful biomarker for diagnosis of inherited disorders of propionate metabolism, but its utility in guiding the adjustment of treatment regimens and in predicting the metabolic status still needs to be established, with only a few works reporting data on urine/plasma MCA in the follow-up of PA and MMA. 5,[10][11][12][13][14][15] In this study, we have prospectively evaluated plasma concentrations of MCA and its correlations with primary and secondary biomarkers, including FGF21, in a large series of PA and MMA patients, on standard treatment and/or after transplantation, to explore the potential contribution of MCA quantification in the long-term management of organic acidemias.…”
Section: Introductionmentioning
confidence: 99%
“…Propionylcarnitine (C3) is a disease biomarker but can display variable elevations in the context of newborn screening for MMA and PA. From a methodological perspective sensitivity and specificity for diagnosis of MMA and PA from dried blood spots, obtained during the first days of life, can be optimised by measuring C3/C2 ratio, 2‐methylcitrate, 17‐19 3‐hydroxypropionate, 20 C3/C0 and C16:1OH/C2 21 and C17, 22 either as part of the initial screening or as second tier testing.…”
Section: Guidelinesmentioning
confidence: 99%
“…The extraction of total FAs from a diminutive plasma volume (10 μL) was done as previously described [ 25 ]. Coupling of DAABD-AE with FAs was achieved using published conditions with minor modifications to accommodate the qualitative and quantitative diversity of analytes in this study [ 20 , 21 , 25 , 35 , 36 ]. This modification involved a facile single-step derivatization protocol that involves the use of premixed reagents added directly to the residual plasma extract followed by incubation at 60 °C for 1 h. When various DAABD-AE concentrations were tested, we confirmed that 2.0 mmol/L is adequate to achieve the desired derivatization yield.…”
Section: Resultsmentioning
confidence: 99%
“…With liquid chromatography (LC) as a front-end technology, LC-MS/MS methods represent powerful alternatives to GC and GC-MS due to the simpler workflow, better sensitivity, and faster analytical time [ 17 ]. Over the past years, applications of LC-MS/MS have expanded significantly in clinical laboratories in areas, such as therapeutic drug monitoring, drugs of abuse, clinical toxicology, and inborn errors of metabolism [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%